Prospection des eaux souterraines dans la région de Niellé (Nord de la Côte d’Ivoire): Efficience de la méthode de résistivité électrique - Kouakou, Kouassi Eric-Germain; Kouadio, Konan Emmanuel; Keita, Diaratou; Kouame, Loukou Nicolas; Sombo, Abe Parfait (European Scientific Journal, ESJ, 2017)
The National Office of Drinking Water (ONEP) has initiated a study at Niellé to strengthen the drinking water production capacity of this locality. The aim of this study is to identify cracks aquifers for the choice of highflowrate drill sites. The study consists in an analysis previous drilling, a prospective study by geophysics and selection of drilling sites. This work shows that the hydraulically active fractures in the region is optimal in the upper part of the fissured horizon located in the first thirty meters under saprolites. The electrical method was used to locate and characterize fractures in various directions including those oriented N164 °, N100 ° and N86 °. They were selected for the drilling site choice. A drilling was carried out with an hourly flow rate of 10.2 m3 / h. This work also showed that the fracture- geomorphological combination the combined study of fracking and geomorphological analysis allows precise selection of drilling sites.